Frame-Based Change Detection Using Histogram and Threshold to Separate Moving Objects from Dynamic Background - Jasim, Hala A.; George, Loay E.; Abd-almajied, Mohammed I. (Iraqi Journal of Science, 2024)
Detecting and subtracting the Motion objects from backgrounds is one of the most important areas. The development of cameras and their widespread use in most areas of security, surveillance, and others made face this problem. The difficulty of this area is unstable in the classification of the pixels (foreground or background). This paper proposed a suggested background subtraction algorithm based on the histogram. The classification threshold is adaptively calculated according to many tests. The performance of the proposed algorithms was compared with state-of-the-art methods in complex dynamic scenes.